Analisis Faktor-Faktor Yang Memengaruhi Kinerja Pegawai RSUD Grati Kabupaten Pasuruan - Risqi Isnia Sabrina; Widi Hariyanti; Faiz Rahman Siddiq (Jurnal Bisnis dan Kewirausahaan, 2024)
The purpose of this research to analyze affecting factors of employee performance at Grati General Hospital Kabupaten Pasuruan. The analysis in this research uses independent variables were organizational commitment, organizational culture, motivasion, and work dicipline.The sample in this research were employees in every department at Grat General Hospital Kabupten Pasuruan. Data collection methods used a questionnaires. Data quality test in this research used the R2 test, F test, and T test. The result of this research indicate that variable organizational commitment, organizational culture, and motivation does not effect the employees performance while the variable work dicipline has a significant effect on employee performance.